A quantitative assay for the assessment of cutaneous human papillomaviruses and polyomaviruses over time: A proof-of-concept in two patients with atopic dermatitis and psoriasis. - Aurélie Du-Thanh; Vincent Foulongne; Olivier Dereure; Marc Eloit; Philippe Pérot (PLoS ONE, 2024)
The human skin virome, unlike commensal bacteria, is an under investigated component of the human skin microbiome. We developed a sensitive, quantitative assay to detect cutaneous human resident papillomaviruses (HPV) and polyomaviruses (HPyV) and we first used it to describe these viral populations at the skin surface of two patients with atopic dermatitis (AD) and psoriasis (PSO). We performed skin swabs on lesional and non-lesional skin in one AD and one PSO patient at M0, M1 and M3. After extraction, DNA was amplified using an original multiplex PCR technique before high throughput sequencing (HTS) of the amplicons (named AmpliSeq-HTS). Quantitative results were ultimately compared with monoplex quantitative PCRs (qPCRs) for previously detected viruses and were significantly correlated (R2 = 0.95, ρ = 0.75). Fifteen and 13 HPV types (mainly gamma and beta-HPVs) or HPyV species (mainly Merkel Cell Polyomavirus (MCPyV)) were detected on the skin of the AD and PSO patients, respectively. In both patients, the composition of the viral flora was variable across body sites but remained stable over time in non-lesional skin samples, mostly colonized with gamma-papillomaviruses. In lesional skin samples, beta-papillomaviruses and MCPyV were the major components of a viral flora more prone to vary over time especially with treatment and subsequent clinical improvement. We believe this method might be further used in extensive studies to further enhance the concept of an individual cutaneous viral fingerprint and the putative role of its alterations through various skin diseases and their treatments.